Case Report: Heterozygous ADAR c.3019G>A pathogenic variant associated with variable neurological symptoms and incomplete penetrance in a four-generational family - Bauer, Ann-Kathrin; Marquardt, Iris; Sundermann, Benedikt; Wolf, Christine; Raupach, Katrin; Grundmann-Hauser, Kathrin; Gieldon, Laura; Otterbach, Maximilian; Maurer, Martin; Haack, Tobias; Lee-Kirsch, Min Ae; Korenke, Georg-Christoph; et al. (Frontiers in Immunology, 2025)
Heterozygous pathogenic variants in ADAR have been associated with dyschromatosis symmetrica hereditaria, while biallelic pathogenic variants have been associated with Aicardi-Goutières syndrome 6 (AGS6). However, the heterozygous variant c.3019G>A, (p.Gly1007Arg) has been described to cause neurological manifestations, which resemble AGS6 and are associated with an upregulation of interferon-stimulated genes. We report a four-generation family with two symptomatic family members and five unaffected carriers of the heterozygous pathogenic ADAR variant c.3019G>A. The index (patient 1) manifested a gait disorder at three years of age (weakness in his legs, a tendency to fall and hyperreflexia), dyslalia, and mild cognitive developmental delay. A paternal half-brother (patient 4) to patient´s father (patient 2) presented with irritability and regression of previous skills at the age of 6 months after a fever reaction, following the second routine hexavalent vaccination at the age of 4 months. At 20 years of age, the patient was wheelchair-bound, had spasticity and severe global development delay. A blood test in both patients showed increased interferon signature with activation of type 1-interferon. Five asymptomatic carriers were identified in this family (age range 2–81 years of age) nearly all of them (except the 81-year old patient) showed a strong activation of type 1 interferon response in peripheral blood. Affected individuals had higher interferon signature than asymptomatic, underlining the possible role of interferon activation in disease mechanism. To our knowledge, this is the biggest family reported to date, encompassing a wide age-range of carriers, including an asymptotic carrier of advanced age (81 years of age).